Stress inducible proteinase inhibitor diversity in capsicum annuum - Mishra, Manasi; Mahajan, Neha S.; Tamhane, Vaijayanti A.; Kulkarni, Mahesh J.; Baldwin, Ian T.; Gupta, Vidya S.; Giri, Ashok P. (BMC Plant Biology, 2012)
Background: Wound-inducible Pin-II Proteinase inhibitors (PIs) are one of the important plant serine PIs which have been studied extensively for their structural and functional diversity and relevance in plant defense against insect pests. To explore the functional specialization of an array of Capsicum annuum (L.) proteinase inhibitor (CanPIs) genes, we studied their expression, processing and tissue-specific distribution under steady-state and induced conditions. Inductions were performed by subjecting C. annuum leaves to various treatments, namely aphid infestation or mechanical wounding followed by treatment with either oral secretion (OS) of Helicoverpa armigera or water. Results: The elicitation treatments regulated the accumulation of CanPIs corresponding to 4-, 3-, and 2-inhibitory repeat domains (IRDs). Fourty seven different CanPI genes composed of 28 unique IRDs were identified in total along with those reported earlier. The CanPI gene pool either from uninduced or induced leaves was dominated by 3-IRD PIs and trypsin inhibitory domains. Also a major contribution by 4-IRD CanPI genes possessing trypsin and chymotrypsin inhibitor domains was specifically revealed in wounded leaves treated with OS. Wounding displayed the highest number of unique CanPIs while wounding with OS treatment resulted in the high accumulation of specifically CanPI-4, -7 and -10. Characterization of the PI protein activity through two dimensional gel electrophoresis revealed tissue and induction specific patterns. Consistent with transcript abundance, wound plus OS or water treated C. annuum leaves exhibited significantly higher PI activity and isoform diversity contributed by 3- and 4-IRD CanPIs. CanPI accumulation and activity was weakly elicited by aphid infestation yet resulted in the higher expression of CanPI-26, -41 and -43. Conclusions: Plants can differentially perceive various kinds of insect attacks and respond appropriately through activating plant defenses including regulation of PIs at transcriptional and post-translational levels. Based on the differentially elicited CanPI accumulation patterns, it is intriguing to speculate that generating sequence diversity in the form of multi-IRD PIs is a part of elaborative plant defense strategy to obtain a diverse pool of functional units to confine insect attack.
Keywords: CanPI; Herbivory; Oral secretions; Pin-II type proteinase inhibitors; Plant-insect interaction

Silencing an N-acyltransferase-like involved in lignin biosynthesis in nicotiana attenuata dramatically alters herbivory-induced phenolamide metabolism - Gaquerel, Emmanuel; Kotkar, Hemlata; Onkokesung, Nawaporn; Galis, Ivan; Baldwin, Ian T. (Plos One, 2013)
In a transcriptomic screen of Manduca sexta-induced N-acyltransferases in leaves of Nicotiana attenuata, we identified an N-acyltransferase gene sharing a high similarity with the tobacco lignin-biosynthetic hydroxycinnamoyl-CoA: shikimate/quinate hydroxycinnamoyl transferase (HCT) gene whose expression is controlled by MYB8, a transcription factor that regulates the production of phenylpropanoid polyamine conjugates (phenolamides, PAs). To evaluate the involvement of this HCT-like gene in lignin production as well as the resulting crosstalk with PA metabolism during insect herbivory, we transiently silenced (by VIGs) the expression of this gene and performed non-targeted (UHPLC-ESI/TOF-MS) metabolomics analyses. In agreement with a conserved function of N. attenuata HCT-like in lignin biogenesis, HCT-silenced plants developed weak, soft stems with greatly reduced lignin contents. Metabolic profiling demonstrated large shifts (up to 12% deregulation in total extracted ions in insect-attacked leaves) due to a large diversion of activated coumaric acid units into the production of developmentally and herbivory-induced coumaroyl-containing PAs (N', N `'-dicoumaroylspermidine, N', N `'-coumaroylputrescine, etc) and to minor increases in the most abundant free phenolics (chlorogenic and cryptochlorogenic acids), all without altering the production of well characterized herbivory-responsive caffeoyl-and feruloyl-based putrescine and spermidine PAs. These data are consistent with a strong metabolic tension, exacerbated during herbivory, over the allocation of coumaroyl-CoA units among lignin and unusual coumaroyl-containing PAs, and rule out a role for HCT-LIKE in tuning the herbivory-induced accumulation of other PAs. Additionally, these results are consistent with a role for lignification as an induced anti-herbivore defense.